2019
DOI: 10.1007/s11548-019-02080-3
|View full text |Cite
|
Sign up to set email alerts
|

Body-mounted robotic assistant for MRI-guided low back pain injection

Abstract: Purpose-This paper presents the development of a body-mounted robotic assistant for magnetic resonance imaging (MRI)-guided low back pain injection. Our goal was to eliminate the radiation exposure of traditional X-ray guided procedures while enabling the exquisite image quality available under MRI. The robot is designed with a compact and lightweight profile that can be mounted directly on the patient's lower back via straps, thus minimizing the effect of patient motion by moving along with the patient. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The experiment results indicate four main factors that lead to the cannula placement errors of the robot-assisted approach: (1) mechanism errors, including fabrication/assembly tolerance, backlash of timing belts, deformation of plastic materials, etc., (2) imaging errors, including image resolution, registration accuracy, cannula artifacts, etc., (3) skin elasticity variations at the entry point, and (4) cannula bending. The error sources of the mechanism and imaging factors were analyzed in our previous study on free space evaluation and MRI phantom study with a reported target position error of 1.70±0.21mm and insertion angle error of 0.66±0.43 • [23]. Significant skin deformation at the entry point was observed during the initial test insertions into the cadaver, especially as the tissue dried out over the time, which caused bending and deviation of the cannula trajectory and consequently failure of reaching targets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment results indicate four main factors that lead to the cannula placement errors of the robot-assisted approach: (1) mechanism errors, including fabrication/assembly tolerance, backlash of timing belts, deformation of plastic materials, etc., (2) imaging errors, including image resolution, registration accuracy, cannula artifacts, etc., (3) skin elasticity variations at the entry point, and (4) cannula bending. The error sources of the mechanism and imaging factors were analyzed in our previous study on free space evaluation and MRI phantom study with a reported target position error of 1.70±0.21mm and insertion angle error of 0.66±0.43 • [23]. Significant skin deformation at the entry point was observed during the initial test insertions into the cadaver, especially as the tissue dried out over the time, which caused bending and deviation of the cannula trajectory and consequently failure of reaching targets.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this system is considered to be an MRI-Conditional system. A detailed description of the mechanical design is reported in [23].…”
Section: Mr-conditional Cannula Placement Manipulatormentioning
confidence: 99%
See 2 more Smart Citations
“…7 Body-mounted robotic assistant for magnetic resonance imaging (MRI)-guided low back pain injections is another budding modality in the armamentarium for refractory low back pain without exposure to radiation. 8 General anesthesia is usually preferred for all kinds of surgical procedures involving the spine due to better patient tolerance, secure airway, better surgical exposure under muscle relaxants, early postoperative exam without the confounding results from conventional epidural anesthetic agents, and better control of intraoperative hemodynamic changes. However, it has its own risks, particularly in patients with increased age and cardiopulmonary disorders.…”
Section: Introductionmentioning
confidence: 99%